Analisis Integrasi Kebijakan Hukum Pariwisata dalam Pelaksanaan Layanan Bimbingan Konseling untuk Penguatan Pendidikan Karakter Siswa : Penelitian - Saputra, Ridho Indra; Insaniyah, Insaniyah; Hidayati, Annisa; Vikra, Zulfa Asma (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the integration of tourism values and legal regulations in the implementation of Guidance and Counseling (BK) services for character building in inclusive schools. This qualitative study employs a case study design conducted at SDIT Permata Jannati Banjarmasin, involving BK teachers, classroom teachers, school principals, parents, and students with special needs as research subjects selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and document analysis, and analyzed using the Miles, Huberman, and Saldaña model through data reduction, presentation, and conclusion drawing. The results indicate that BK services are well-structured and utilize educational tourism activities to instill ethical values, environmental awareness, and respect for local culture. Legal tourism regulations provide a normative framework that supports this practice, although challenges remain due to the absence of official guidelines for counselors. The study confirms that integrating tourism, law, and BK services can serve as an effective strategy for contextual and applicable character education.